READING AND REREADING: INSIGHTS INTO LITERARY EVALUATION - Willie van Peer; Anna Chesnokova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
In this paper, we argue that the long-term evaluation of literary texts rather privileges their formal and structural aspects, but to a lesser degree the content. As external and internal reasons for literary evaluation are distinguished, the latter are privileged while the former will only last as the themes and the external reasons remain, which means they are transient and do not lead to long-term evaluation of literary products. At the same time, it is the second type of internal reasons - the form and structure of a literary work - that plays a role and contributes to canon formation. Hence we present the results of some experiments in which two different groups of participants (university students and older people in a convenience sample) in two cultural settings read three texts (one popular fiction and two canonical ones) several times and answered the three questions derived from the "rereading paradigm" by Bortolussi & Dixon (2003). As an additional measure to check the participants reading habits, in Study 1 the ART test from Stanovich et al. (1995), adapted for a Ukrainian audience, was employed. The results, which did not corroborate the predictions, are discussed and confronted with some insights into the theory of literary evaluation.